Structural and electrical characterizations of cerium (Ce3+)-doped double perovskite system Sr2NiMoO6−δ - Kumar P.; Singh N.K.; Sinha A.S.K.; Singh P. (My University, 2025)
The double perovskite system Sr2−xCexNiMoO6−δ (SCNM) with 0.01 ≤ x ≤ 0.05 was synthesized by the citrate–nitrate auto-combustion synthesis route. Thermal studies were carried out by simultaneous differential scanning calorimetry and thermal gravimetry. Phase constitution was analyzed by powder X-ray diffraction (XRD). Rietveld refinement showed that the major phase exists in tetragonal form with space group I4/m. Microstructural investigations revealed the formation of uniform grains. The electrical conductivity studied by impedance spectroscopy in the temperature range 300–600 °C was found to follow a thermally activated process. The sample with x = 0.01 showed the highest conductivity with lowest activation energy. The electrical conductivity of the system was discussed in terms of identified impurity phases and charge density [MoMo6+5+′]. The variation of electrical conductivity with composition was explained on the basis of X-ray photoelectron spectroscopy and XRD studies. © 2016, Springer-Verlag Berlin Heidelberg.